SKILL, CRAFT AND HISTORIES OF INDUSTRIALISATION IN EUROPE AND ASIA*. (24th October 2014) - Berg, Maxine
ABSTRACT: It is time to reexamine craft and small-scale manufacture within our histories of industrialisation, both West and East, and to reflect on the long survival and adaptation of artisanal production even within our globalised world of production and consumption. Historians since the 1950s have addressed craft, skill and labour-intensive production in historical frameworks such as 'the rise of the factory system', 'proto-industrialisation' and 'flexible specialisation'. More recently, they have devised other concepts which include labour and skill-intensive production such as 'industrious revolution', 'the great divergence', 'knowledge economies', 'East Asian development paths' and 'cycles of production'. This paper surveys this historiography of craft and skill in models of industrialisation. It then reflects on small-scale industrial structures in current globalisation, emphasising the continued significance of craft and skill over a long history of global transitions. It gives close examination to one region, Gujarat, and its recent industrial and global history. The paper compares industrial production for East India Company trade in the eighteenth century to the recent engagement of the artisans of the Kachchh district of Gujarat in global markets. It draws on the oral histories of seventy-five artisan families to discuss the past and future of craft and skill in the industry of the global economy.